2003
DOI: 10.1519/00124278-200308000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of Eccentric Actions on Net Caloric Cost Resulting From Isoinertial Resistance Exercise

Abstract: Net O 2 uptake was measured from maximal-effort 3-set, 8repetition seated leg press protocols on an isoinertial ergometer. Subjects (25 women, 9 men) did 2 workouts each exerting concentric-eccentric (CE) and concentric-only (CO) knee extensor forces to measure work and net caloric cost. Significant (p Ͻ 0.05) relationships between work and net caloric cost resulted from CE and CO workouts for the male, female, and total subject sample. Two-way repeated-measures analyses of variance showed CE workouts resulted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1
6

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 23 publications
0
11
1
6
Order By: Relevance
“…Despite similar CE3 and CO6 TW values, only the latter yielded higher [C] than CO3, which suggests eccentric actions blunt [C]. Prior work shows a lower metabolic cost from eccentric actions (9,13). Perhaps [C] changes from eccentric actions are dictated by metabolic factors in addition to TW.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Despite similar CE3 and CO6 TW values, only the latter yielded higher [C] than CO3, which suggests eccentric actions blunt [C]. Prior work shows a lower metabolic cost from eccentric actions (9,13). Perhaps [C] changes from eccentric actions are dictated by metabolic factors in addition to TW.…”
Section: Discussionmentioning
confidence: 85%
“…Metabolism research showed eccentric actions evoked 1/7th the net energy cost of muscle shortening from leg presses done on standard equipment (13). In a similar fashion, eccentric FERG leg press actions added no net caloric cost beyond that from concentric exercise (9). It was concluded the CE3 protocol uses stored elastic energy to evoke muscle potentiation and stretch reflexes with eccentric FERG actions (9).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…A similar seated leg press study was then conducted with a fl ywheel ergometer, specifi cally designed for use as in-fl ight hardware ( 5 ). The radii of the fl ywheels imposed a large inertial load that enabled performance of low-speed high-resistance repetitions, in contrast to the manner muscle actions are performed on the Impulse.…”
Section: Discussionmentioning
confidence: 99%